POSSIBILITIES OF MIRR METHOD APPLICATION FOR EVALUATION OF INVESTMENTS IN AGRICULTURE: AN EXAMPLE OF PIGS FATTENING - Ivanović, Sanjin; Nastić, Lana; Bekic, Bojana (Economics of Agriculture, 2015)
In the case of some agricultural investments, often net cash flow changes its sign from positive to negative, many times during the project. It causes the problem of internal rate of return calculation, which is an important indicator of economic effectiveness of investments. That is, in such situations, internal rate of return cannot be used. To solve this problem, modified rate of return is applied. This paper aimed to describe this method in detail, and to show its calculation for investments in pigs fattening. By application of modifed internal rate of return it is determined that pigs fattening, under assumed conditions, is economically justifed. Also, authors calculated the upper limit of discount rate (cost of capital), to which investment in pigs fattening is economically justifed. It is concluded that, in the case of specifc agricultural investments (such as pigs fattening), the use of traditional internal rate of return could give the wrong image on actual rate of return on investments.